Sistem Absensi QR Code Dengan Integrasi Telegram Berbasis Android Pada Toko Produk Tas Bogor - Muhamad Febriyanto; Maulana Muhamad Sulaiman (CV. Multi Kreasi Media, 2025)
Toko Produk Tas Bogor is a UMKM in Bogor City engaged in home-based businesses. Toko Produk Tas Bogor was established in 2017. This shop sells various types of Fashion goods. In the internal Toko Produk Tas Bogor, there is a problem with employee attendance. It still uses manual attendance, and the administrator who recapitulates attendance takes too long to collect attendance forms. From these problems, researchers made an Android-based application that uses QR Code and integration using Telegram, this research uses the Waterfall method, and data collection based on field studies, observations, interviews, and literature studies. The results of this study can help employees take attendance digitally, increase efficiency and accuracy in the attendance list, and reduce fraud in falsifying attendance data.